ASUHAN KEBIDANAN PADA NN. T DENGAN DISMENOREA PRIMER: LAPORAN KASUS - Theyhana Qory Tila Thabrani; Dedes Fitria (Politeknik Kesehatan Kemenkes Bandung, 2024)
The menstrual disorder that teenagers often experienced was dysmenorrhoea, so it must receive appropriate treatment because it is related to one of the causes of teenage girls' absence from school. The prevalence of primary type dysmenorrhea in Indonesia is 6 times higher than secondary type dysmenorrhea. In reproductive health care, midwives detect signs and symptoms and provide education to clients. The method used in writing this report is a case report. Data collection techniques from interviews, physical examination, observation, documentation studies, and literature studies. The report documentation use SOAP. The results of the research obtained subjective data from Mrs. T came on the second day of menstruation with complaints of pain in the lower abdomen, pain in the waist and hips every time during menstruate on days 1-3. Objective data showed a tenderness in the lower abdomen. The analysis was Mrs. T 14 years old with primary dysmenorrhoea. The intervention provided include measuring the pain scale using the NRS instrument with NRS score 3, education, dysmenorrhoea exercises, giving Fe, as well as management principle of pain reduction. The conclusion from the intervention given was that there was a decrease in the scale of pain during menstruation. However, there is a gap because there are no fixed procedures for treating dysmenorrhoea. The advice given to Mrs. T was to carry out the services provided to reduce pain during menstruation, suggestions for health services and midwives to improve the quality of providing education regarding reproductive health in accordance with established procedures.